Intersections of Culture, Migration and Intimate Partner Violence as Told by Migrant Youth - Mayeda, David Tokiharu; Vijaykumar, Raagini (International Journal of Criminology and Sociology, 2015)
Like many other western nations, New Zealand has experienced significant migration since the mid-1980s. According to the most recent census, roughly one out of every four persons living in New Zealand is foreign born. The significant number of migrants to New Zealand of Asian and Middle Eastern ancestries has led to the development of rich and diverse ethnic enclaves. However, young people from these communities experience significant pressures to assimilate into western culture, which sometimes clash with parental desires to perpetuate cultural traditions. Drawing on 10 small group interviews conducted with 11 adolescent and 16 young adult female interviewees of Asian and Middle Eastern backgrounds in Auckland, New Zealand, this study examines how participants traverse culturally prescribed gender roles as they relate to intimate partner violence (IPV). Emergent themes from the study address participants’ conceptualization of IPV, processes of learning IPV, and pressures to follow rigid gender-roles tied to IPV that are culturally embedded. The article closes with discussion on interpretation of research findings without perpetuating an Orientalist framework.